The role of psychological factors in the alpine skiing learning process of the ski beginners - Cigrovski, V.; Matkovic, B.; Matkovic, B.; Ivanec, D. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: The role that psychological factors play in influencing sports in general has received much attention in recent sports literature (Cartoni et al. 2005; Pallesen et al. 2006). In this study, the influence of fear, self-efficacy, and worry experienced by young people wishing to learn alpine skiing was investigated.